2021
DOI: 10.3389/fnins.2021.685774
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Intersubject Correlations Reflect Selective Attention in a Competing Speaker Scenario

Abstract: Several solutions have been proposed to study the relationship between ongoing brain activity and natural sensory stimuli, such as running speech. Computing the intersubject correlation (ISC) has been proposed as one possible approach. Previous evidence suggests that ISCs between the participants’ electroencephalogram (EEG) may be modulated by attention. The current study addressed this question in a competing-speaker paradigm, where participants (N = 41) had to attend to one of two concurrently presented spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 45 publications
5
21
1
Order By: Relevance
“…We observed that ISC was stronger during story listening compared to rest for all three spatial components. This is consistent with previous studies showing that ISC is stronger when attending to a coherent narrative compared to when attention is directed elsewhere (S. S. Cohen et al, 2018; Ki et al, 2016; Kuhlen et al, 2012; Rosenkranz et al, 2021) or compared to rest (Hasson et al, 2004; Wilson et al, 2008). Inter-subject correlation is often thought of as a neural signature of engagement, because ISC is stronger for captivating or exciting stimuli (Hasson et al, 2010; Schmälzle et al, 2015) and predicts behavioral engagement measures (S. S. Cohen et al, 2017; Dikker et al, 2017; Dmochowski et al, 2014; Poulsen et al, 2017; Song et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that ISC was stronger during story listening compared to rest for all three spatial components. This is consistent with previous studies showing that ISC is stronger when attending to a coherent narrative compared to when attention is directed elsewhere (S. S. Cohen et al, 2018; Ki et al, 2016; Kuhlen et al, 2012; Rosenkranz et al, 2021) or compared to rest (Hasson et al, 2004; Wilson et al, 2008). Inter-subject correlation is often thought of as a neural signature of engagement, because ISC is stronger for captivating or exciting stimuli (Hasson et al, 2010; Schmälzle et al, 2015) and predicts behavioral engagement measures (S. S. Cohen et al, 2017; Dikker et al, 2017; Dmochowski et al, 2014; Poulsen et al, 2017; Song et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that ISC was stronger during story listening compared to rest for all three spatial components. This is consistent with previous studies showing that ISC is stronger when attending to a coherent narrative compared to when attention is directed elsewhere (Cohen et al, 2018;Ki et al, 2016;Kuhlen et al, 2012;Rosenkranz et al, 2021) or compared to rest (Hasson et al, 2004;Wilson et al, 2008). Observing significant ISC despite the presence of background noise suggests that participants were able to remain engaged despite presumably missing bits of the story during periods when the SNR was low.…”
Section: Speech Intelligibility Declines With Decreasing Signal To Noise Ratiosupporting
confidence: 91%
See 1 more Smart Citation
“…However, despite being highly significant at the group-level, this effect was not ubiquitous across all participants, and was statistically significant only in a subset of participants (∼30%). To the best of our knowledge, previous studies have not directly addressed this inter-subject variance in attentional-bias, however several pervious papers that present individual-level data seem to exhibit similar variability (Ding and Simon 2012a, 2012b; Fuglsang et al 2017; Rosenkranz et al 2021). In the current data set, inter-subject variability in the magnitude of attentional bias was not correlated with working memory capacity (OSPAN), which sometimes drives individual differences in attentional abilities (Beaman et al 2007; Sörqvist and Rönnberg 2014a; Lambez et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Previous work considered CorrCA components corresponding to three highest ISC values [32]. In this work…”
Section: Resultsmentioning
confidence: 99%